REPORT OF ENTOMOPATHOGENIC FUNGI, BEAUVERIA BASSIANA, AND METARHIZIUM RILEYI FROM CHOTANAGPUR PLATEAU, INDIA - CECILIA K. BARLA; AJAY SHARMA; S. MAURYA (The Bioscan, 2021)
The occurrence of entomopathogenic fungi has been reported from different parts of India, but very few from Jharkhand. Therefore, keeping the above fact in mind, a study on the survey and collection of entomopathogenic fungi from different areas of Ranchi district was done. On the basis of the macroscopic and microscopic examination of spore attributes under the phase contrast microscope, the isolated entomopathogenic fungal genera were determined to be Beauveria bassiana and Metarhizium rileyi . B.bassiana mycelium was septate, white hyaline, smooth walled, with round conidia measuring 3-5μ in diameter; culture showed a dispersed growth pattern, round with raised elevation, and a white smooth powdery texture. M.rileyi showed septate, hyaline mycelium, short conidiogenous cells, cylindrical conidia measuring 5m-9μm long, a radial colony, smooth texture, and whitish to greenish colour. The natural occurrence of entomopathogenic fungi during a particular period of time explains their dependency upon factors such as climate, habitat, etc., as well as the outbreak of pests that can cause a heavy infestation of fungi. Keeping in mind their ability to parasitize and kill their hosts, these pathogens can be utilised as agents in the biocontrol of insect pests.